First report of three genera of fairyflies (Hymenoptera: Mymaridae) from India with description of a new species of Dicopus and some other records - Manickavasagam, S.; Rameshkumar, A. (Zootaxa, 2011)
Dicopomorpha Ogloblin, Dicopus Enock and Omyomymar Schauff (Hymenoptera: Mymaridae) are recorded from India for the first time and one new species, Dicopus noyesi Manickavasagam, sp. nov., is described from material collected from the state of Tamil Nadu. Gonatocerus bicoloriventris Zeya, G. breviterebratus Subba Rao, G. shamimi Subba Rao and Hayat, Mymar schwanni Girault, Narayanella thornypoda (Narayanan & Subba Rao) and Polynema mendeli Girault (Mymaridae) are also newly recorded from the state of Tamil Nadu.